2016
DOI: 10.3126/jmrd.v2i1.16215
|View full text |Cite
|
Sign up to set email alerts
|

Studies on food preferences of maize weevil, Sitophilus zeamais Mots. to different crops in Chitwan, Nepal

Abstract: Food preference by the maize weevil, Sitophilus zeamais Motschulsky was studied on seven different crops and varieties including maize, wheat and rice. They were maize cultivars namely Arun-2, Manakamana-4, Deuti, buckwheat local cultivar, wheat cultivar namely Annapurna-1, polished rice-Radha 4 and unshelled rice cultivar Mansuli under storage condition at Institute of Agriculture and Animal Science, Rampur, Chitwan, Nepal from June 2013 to February 2014 . The hosts were tested using completely randomized des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…Research has demonstrated that the maize weevil pest has shown preference to other products other than maize under certain storage conditions. Wheat and polished rice were most preferred to maize, buckwheat and paddy while rice paddy and buckwheat were least preferred [30]. In a different study on Italian diets, superfine and parboiled rice were more preferred than other rice categories and on the contrary, pre-cooked rice and enriched rice were less attractive to S. zeamais adults.…”
Section: Host Preferencementioning
confidence: 89%
“…Research has demonstrated that the maize weevil pest has shown preference to other products other than maize under certain storage conditions. Wheat and polished rice were most preferred to maize, buckwheat and paddy while rice paddy and buckwheat were least preferred [30]. In a different study on Italian diets, superfine and parboiled rice were more preferred than other rice categories and on the contrary, pre-cooked rice and enriched rice were less attractive to S. zeamais adults.…”
Section: Host Preferencementioning
confidence: 89%
“…), triticale (Triticum aestivum L. and Secale cereale) and barley (Hordeum vulgare). 165 De Lira et al 166 investigated the fumigant toxicity of the inorescence essential oil obtained from Alpinia purpurata against Sitophilus zeamais adults with an LC 50 value of 41.4 mL per L in air. 166 The insecticidal property is mainly related to b-pinene, apinene, methyl cinnamate, a-terpineol and camphor as the major compounds presented in Alpinia essential oils.…”
Section: Insecticidal Activitymentioning
confidence: 99%
“…), triticale ( Triticum aestivum L. and Secale cereale ) and barley ( Hordeum vulgare ). 165 De Lira et al 166 investigated the fumigant toxicity of the inflorescence essential oil obtained from Alpinia purpurata against Sitophilus zeamais adults with an LC 50 value of 41.4 mL per L in air. 166 …”
Section: Biological Activities Of Alpinia Oilsmentioning
confidence: 99%
“…is is a coleopteron insect that feeds on the kernel starch of harvested corn, causing quality, and weight loss [4]. Sitophilus zeamais is believed to cause losses of 20-80% in tropical countries [5], but losses of 18-40% have been reported in the Chitwan region of Nepal [6].…”
Section: Introductionmentioning
confidence: 99%